Use of a microelectrode array to record extracellular pacemaker potentials from the gastrointestinal tracts of the ICR mouse and house musk shrew (Suncus murinus). (June 2019) - Liu, Julia Y.H.; Du, Peng; Chan, Wood Yee; Rudd, John A.
Graphical abstract: Highlights: Gut slow waves are calcium currents generated by the interstitial cells of Cajal. It is sensitive to temperature and extracellular electrolyte levels. Its frequency increases with temperature and extracellular calcium levels. Its frequency differs between the stomach and small intestine. The microelectrode array allows spectral analysis for the propagation of slow waves. Abstract: Background: The rhythmic contraction and relaxation of smooth muscles in the gastrointestinal (GI) tract is governed by pacemaker electrical potentials, also termed slow waves, which are calcium currents generated by interstitial cells of Cajal (ICCs). Malfunction of pacemaker rhythms contributes to a number of clinically challenging gastrointestinal motility disorders. Method: A microelectrode array (MEA) was used to record slow waves in vitro from intact GI tissues freshly isolated from the ICR mouse and Suncus murinus . The effects of temperature, extracellular calcium and potassium concentrations on pacemaker potentials were quantified using spatiotemporal metrics. Results: Pacemaker frequency decreased from the duodenum to the ileum in the mouse, but this phenomenon was less significant in Suncus murinus . In both the mouse and Suncus murinus, the stomach had a much lower pacemaker frequency than the intestine. Propagation velocity and amplitude were highest in the proximal intestine. Temperature significantly increased pacemaker frequency in the intestinal tissues of both species. Removal of Ca 2+ from the medium inhibited pacemaker potential and increasing the Ca 2+ concentration increased pacemaker frequency in the mouse ileum. Increasing K + concentration decreased pacemaker frequency in the absence of nifedipine. Conclusions: The MEA allows efficient investigation of gut pacemaker frequency and propagation.